2008
DOI: 10.1080/17439760701760666
|View full text |Cite
|
Sign up to set email alerts
|

Gods or rituals? Relational faith, spiritual discontent, and religious practices as predictors of hope and optimism

Abstract: The current study investigates the incremental validity of a variety of functional religiosity variables such as religious practices, organizations, and self-designations as religious or spiritual, and content variables such as spiritual attachment to one's deity, meaning-making, values/beliefs, and faith maturity to predict unique variance in measures of hope and optimism, above and beyond the variance predicted by the five-factor model of personality. Hierarchical regression analyses revealed that positive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
45
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 55 publications
10
45
2
1
Order By: Relevance
“…In summary, we found that the strength of the students' Trust-in-God was negatively associated with their scores on negative affect and positively associated with their scores on positive affect and feelings of hope. The results of the study support previous findings from other cultures on the positive relationships between Trust-in-God, hope, and positive affect (Bush et al 1999;Büssing and Mundle 2009;Ciarrocchi et al 2008;Lewis and Cruise 2006;Mickley et al 1992;Van Ness and Larson 2002). According to Feldman and Snyder (2005), hope is a glimpse into the nature of the meaning of life, and spirituality has been seen as a path directing one to find meaning in life (Büssing et al 2007a, b).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In summary, we found that the strength of the students' Trust-in-God was negatively associated with their scores on negative affect and positively associated with their scores on positive affect and feelings of hope. The results of the study support previous findings from other cultures on the positive relationships between Trust-in-God, hope, and positive affect (Bush et al 1999;Büssing and Mundle 2009;Ciarrocchi et al 2008;Lewis and Cruise 2006;Mickley et al 1992;Van Ness and Larson 2002). According to Feldman and Snyder (2005), hope is a glimpse into the nature of the meaning of life, and spirituality has been seen as a path directing one to find meaning in life (Büssing et al 2007a, b).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, elderly religious people had higher levels of well-being and hope as well as better results on mental and physical health indices than non-religious people of the same age (Van Ness and Larson 2002). Ciarrocchi et al (2008) reported that having a relationship with God and spiritual commitment were positive predictors of hope and optimism. In Büssing and Mundle's (2009) study, depressed patients showed less reliance on God's help than substance abusers, whereas those with high levels of reliance on God's help showed less depression and higher levels of satisfaction with life.…”
Section: Introductionmentioning
confidence: 97%
“…This difference between the two dimensions replicates previous research (Ciarrocchi et al, 2008;Dy-Liacco et al, 2009;Piedmont & Nelson, 2001) and highlights that the horizontal dimension of the FMS is a related, albeit distinct, dimension of spirituality. It is strongly associated with intellect and is also predictive of social relationship and environmental health.…”
Section: Discussionsupporting
confidence: 83%
“…Abramson, Seligman, and Teasdale (1978) and other researchers noted that the style of attributing good events to factors that are stable, global, and internal characterizes an optimistic outlook in life, whereas attributing bad events to the same internal, stable, and global factors characterizes a pessimistic outlook. Recent studies have shown an association of optimism with spiritual commitment, religious affiliation (Ciarrocchi et al, 2008), and intrinsic religiosity (Salsman, Brown, Bretching, & Carlson, 2005). We therefore expected the following:…”
Section: Fms and Social Axiomsmentioning
confidence: 99%
“…희망은 개인이 어떻게 자신의 목표를 성공적으로 이루고자 노력하는가에 대한 보다 폭넓은 설명을 제공한다 (Padilla-Walker, Hardy, & Christensen, 2011). 청소년을 대상으로 한 연구에서 희망은 약물남용 (Carvajal, Clair, Nash, & Evans, 1998), 폭력과 공격 (Bolland, 2003), 성행동 (Chang et al, 2003), 자기 존중감, 삶의 만족, 학업성취를 예언하였고 (Adelabu, 2008;Barnum et al, 1998;You et al, 2008), 사회적지지 (Bland & Darlington, 2002), 내외통제성 (Bunston, Mings, Mackie, & Jones, 1995), 종교 (Ciarrocchi, Dy-Liacco, & Deneke, 2008)등에 의해 예언되었다. 또한 희망은 청소년 의 사회적 지지와 일반적인 안녕감을 매개하였고 (Yarcheski, Mahon, & Yarcheski, 2001), 사회적 지지와 긍정적인 건강행동 사이를 매개하는 것으로도 밝혀졌다 (Mahon, Yarcheski, & Yarcheski, 2004).…”
Section: 학업스트레스와 학업소진의 관계를 매개할 가능성이 있는 여러 가지 변인들 중 본 연구에서 주목하고자 하는 것은unclassified